2018
DOI: 10.1073/pnas.1811837116
|View full text |Cite
|
Sign up to set email alerts
|

In crystallo thermodynamic analysis of conformational change of the topaquinone cofactor in bacterial copper amine oxidase

Abstract: In the catalytic reaction of copper amine oxidase, the protein-derived redox cofactor topaquinone (TPQ) is reduced by an amine substrate to an aminoresorcinol form (TPQamr), which is in equilibrium with a semiquinone radical (TPQsq). The transition from TPQamr to TPQsq is an endothermic process, accompanied by a significant conformational change of the cofactor. We employed the humid air and glue-coating (HAG) method to capture the equilibrium mixture of TPQamr and TPQsq in noncryocooled crystals of the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 27 publications
7
23
0
Order By: Relevance
“…We found that the experimentally determined crystal structure was best reproduced by the −H + state with an enolate form of TPQ in the optimized structure 0 − (rmsd = 0.107 Å; SI Appendix, Table S2) and that the keto form of TPQ is accessible in the Full state (1) with only a slightly higher energy (3.1 kcal mol −1 ) than the most stable enolate form of TPQ (0; SI Appendix, Table S2). The free energy change from 0 to 1 was calculated to be 0.69 kcal mol −1 at 298.15 K (SI Appendix, Table S3), well matching the value of 0.21 kcal mol −1 estimated from the occupancy ratio of the enolate (59%) and keto (41%) forms, although the equilibrium state in crystal could be biased by the crystal packing effects and the low temperature under the cryogenic condition (17). In agreement, the smaller rmsd value for 1 (0.167 Å), relative to that for 0 (0.251 Å), supports the formation of the keto form of TPQ (SI Appendix, Fig.…”
Section: Quantum Mechanics/molecular Mechanics Analysis Of the Activesupporting
confidence: 72%
See 1 more Smart Citation
“…We found that the experimentally determined crystal structure was best reproduced by the −H + state with an enolate form of TPQ in the optimized structure 0 − (rmsd = 0.107 Å; SI Appendix, Table S2) and that the keto form of TPQ is accessible in the Full state (1) with only a slightly higher energy (3.1 kcal mol −1 ) than the most stable enolate form of TPQ (0; SI Appendix, Table S2). The free energy change from 0 to 1 was calculated to be 0.69 kcal mol −1 at 298.15 K (SI Appendix, Table S3), well matching the value of 0.21 kcal mol −1 estimated from the occupancy ratio of the enolate (59%) and keto (41%) forms, although the equilibrium state in crystal could be biased by the crystal packing effects and the low temperature under the cryogenic condition (17). In agreement, the smaller rmsd value for 1 (0.167 Å), relative to that for 0 (0.251 Å), supports the formation of the keto form of TPQ (SI Appendix, Fig.…”
Section: Quantum Mechanics/molecular Mechanics Analysis Of the Activesupporting
confidence: 72%
“…Oxidation. We previously demonstrated that crystalline AGAO is catalytically active and yields a semiquinone radical form of reduced TPQ following anaerobic addition of an amine substrate to crystals (8,17). Therefore, the neutron structure determined here likely represents the initial ground state of the enzyme immediately prior to the catalytic reaction.…”
Section: Quantum Mechanics/molecular Mechanics Analysis Of the Activementioning
confidence: 72%
“…The authors found that instead of a single concerted movement across the protein, different parts of the protein have different transition temperatures (Keedy et al, 2015b). Temperature changes have also been used to analyze flavodoxin oxidation states (Watt et al, 1991), and the in crystallo thermodynamics of conformational states of a redox quinone co-factor in bacterial copper amine oxidase during the catalytic reaction (Murakawa et al, 2019). Advances in collecting high-temperature datasets at 293-363 K promise future temperature explorations of the conformational landscape beyond proteinase K, thaumatin, and lysozyme (Doukov et al, 2020).…”
Section: Variable Temperature Crystallographymentioning
confidence: 99%
“…1. 6 In the reductive half-reaction, an oxidative form of TPQ is nucleophilically attacked by the amine substrate, and, via intermediate states of the substrate-and the product-Schiff bases, is reduced to an aminoresorcinol form, which eventually reaches an equilibrium state with a semiquinone radical. Simultaneously the amine substrate is oxidized to the product aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic cycle of AGAO. Proposed states are resting oxidative form (TPQ ox ), substrate Schiff base (TPQ ssb ), product Schiff base (TPQ psb ), aminoresorcinol (TPQ amr ), semiquinone radical (TPQ sq ), and iminoquinone (TPQ imq ) 6. …”
mentioning
confidence: 99%